Improvement in the ability to have sex in patients with Peyronie's disease treated with Collagenase Clostridium histolyticum. Issue 1 (12th October 2022) - Geelhoed, Jeannette P.; Wegelin, Olivier; Tromp, Ellen; de Boer, Bert‐Jan; de Jong, Igle‐Jan; Beck, Jack J. H.
Abstract: Objective: To describe the results of intralesional Collagenase Clostridium histolyticum (CCH) treatment in patients with Peyronie's disease (PD) in real‐world setting. PD is characterized by curvature of the erect penis caused by fibrotic tissue in the tunica albuginea. Patients and methods: Patients with stable PD and curvature of 30° to 90° were prospectively enrolled. CCH injections were initially given using a scheme of four cycles of two injections within 48–72 h every 6 weeks. Later using a modified scheme of three injections every 4 weeks, combined with a vacuum erection device (VED) twice daily. All patients were requested to take pictures of the erect penis prior to and following treatment, from above and laterally. Curvature was measured by three independent researchers based on the provided pictures using a goniometer. Furthermore, patients filled in the Peyronie Disease Questionnaire‐NL (PDQ‐NL) and Patient Reported Outcome Measurement (PROM). The primary outcome was reduction in curvature and the ability to have penetrating sex again. Secondary outcomes include pain scores during injections, changes in PDQ‐NL, PROM and complications of CCH treatment. Results: Sixty‐three patients were included, mean age was 56.0 years (range 39–70) and mean reduction in curvature 20.6° (SD 10.2, range 5–49); 74.5% of the patients were able to have penetrating sex again following treatment, compared with 41.2% prior to treatment. According to the PROM questions, sexual improvement was seen in 66.7% of patients. The satisfaction rate was 6.8 (SD 1.8). All patients save two recommend treatment. Conclusions: Intralesional treatment with CCH in men with PD leads to a mean curvature improvement of 20.6°. Following treatment, 74.5% of men were able to have sexual intercourse and 54.9% of the couples were satisfied with their sex life. No major complications occurred in the patients treated with CCH. CCH is not available in Europe anymore despite good results.